Ceo Charismatic Leadership: Levels-of-Management and Levels-of-Analysis Effects - Waldman, David A.; Yammarino, Francis J. (Academy of Management Review, 1999)
We present a model of CEO charismatic leadership in organizations and show how such leadership can, through levels of management and analysis, impact organizational performance. We integrate levels issues relevant to the conceptualization of theoretical constructs and their relationships, measurement, and echelons, and develop the concept of close versus distant leadership as a means of understanding the dynamics of CEO leadership. We also include a consideration of possible alternative levels of analysis at which the constructs in our model may be operating.